A novel performance evaluation framework for new service development in the healthcare industry using hybrid ISM and ANP - Heidary Dahooie, Jalil; Mohammadi, Navid; Meidutė-Kavaliauskienė, Ieva; Binkytė-Vėlienė, Arūnė (Technological and Economic Development of Economy, 2021)
Today, the innovative activities of companies in new service development (NSD) have an undeniable contribution to the economic development of countries. Given the recent advances in the healthcare industry, the issue of NSD and performance management of firms operating in this industry has received special attention of researchers and decision makers. A review of previous research shows that on the one hand there is no agreement among experts on NSD performance measurement criteria and on the other hand there has been no systematic framework that can measure and manage firm performance in this area. The proposed framework should allow for interaction between different decision makers, considering multiple and sometimes conflicting criteria. In this regard, this paper aimed to provide a framework to assess the NSD performance in healthcare industry using multiple-criteria-decision-making methods. The proposed model consists of 17 different criteria that have been identified and finalized based on previous studies as well as experts’ opinions. Then, the indicators are classified with the help of experts in the form of a balanced scorecard model and presented as an initial model. Due to internal relationships between criteria, this model was evaluated using interpretive structural modelling and modelled at 5 different levels. Then, the analytic network process approach was applied to determine criteria weights. Finally, new service development performance in Moheb hospital was evaluated through the framework proposed here.